If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2xsquared + 4x = 0 Solving 2adeqrsux + 4x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4x' to each side of the equation. 2adeqrsux + 4x + -4x = 0 + -4x Combine like terms: 4x + -4x = 0 2adeqrsux + 0 = 0 + -4x 2adeqrsux = 0 + -4x Remove the zero: 2adeqrsux = -4x Divide each side by '2deqrsux'. a = -2d-1e-1q-1r-1s-1u-1 Simplifying a = -2d-1e-1q-1r-1s-1u-1
| 4b+18+3b=74 | | -54-9b-2b=-10 | | 3/i-9 | | 40+x=5.00 | | 6p-2=10(p-2)-4(14-4p)-6 | | x^17=x^15 | | 16=16+4x | | 10x^6-53x^4+36x^2=0 | | Y-26/9=5/6 | | 7x-4=5-8x | | (6x+1)-(5x-17)-(9x-24)=180 | | =x^4+3x^3-21x^2-33x+110 | | 6x+6(x-4)=9+4x | | 36=-40-2x | | f(-2x)=1.5x+12 | | f(x)=x^4+3x^3-21x^2-33x+110 | | 11/2•3 | | 2x+8-2x-8=0 | | y^2-2y-8x-7=0 | | F(2)=9x-5 | | -3-25a=15 | | 9(3z-1)=18z+45 | | 9(3z-1)=18z+45 | | 7/8*1/4 | | 2x^2+2y^2-12x+9=0 | | 16/5=x-12/25 | | -20-(4x-1)=-51 | | -3/5(7-4x)=25 | | 6x-12=9x-15 | | Xy(2y-3x)= | | -2y-10+2x=o | | gn=3*(-2)n-1 |